Board Composition and Strategic Decision-Making in SMEs: Exploring the Impact of Director Attributes - Francesco Napoli; Domenica Federico; Antonella Notte (Contemporary Research in Business, Management and Economics Vol. 3, 2024)
This paper looks at the problems of strategic change and innovation in small- or medium-sized family firms, both from an empirical and a theoretical point of view. Using a sample of Family-Controlled Small- and medium-sized Companies, the paper shows that strategic change and innovation are complex phenomena and, at the same time, also demonstrate that corporate governance mechanisms are a limited, if significant, part of the variables which influence the firm’s strategic change and innovation. In particular, it is suggested that extending the board and the Top Management Team by involving individuals who do not belong to the dominant family has a positive effect on the firm’s strategic change and innovation. The results from the empirical analysis of the selected sample support the hypotheses. This research has implications for both corporate governance theory and for family owner-managers of SMEs. Adverse environmental conditions and the emergence of new opportunities demand strategic change and innovation and these are often difficult and problematic for the single owner-manager of the family controlled SME to realise. Extending the group of individuals involved in difficult firm decision making may help overcome these difficulties and problems. In particular, adding individuals from outside the controlling family to the board and the TMT may increase capacity to interpret environmental change and extend the capabilities necessary to develop new resources within the firm or, more simply, to combine resources which are already present in new ways and forms. These competences and capabilities are indispensable for any process of strategic change and/or innovation in the firm.